A Inconstitucionalidade da obrigatoriedade da ação penal pública Releitura dos artigos 24 e 28 do Código de Processo Penal e art. 100, §1º, do Código Penal em face da Não Recepção pela Constituição de 1988 - Melo, André Luís Alves de (2017)
The present work proposed to investigate and discuss the unconstitutionality, or not, that is, the non-acceptance of the principle of mandatory public prosecution, in the face of the constitutional principle of functional independence, acting the Public Prosecutor as a political agent in criminal policies And its limits. Sedimented in the innovative proposal of a Doctoral Thesis, the work focused on unconstitutionality (not reception) and not on the convenience or inconvenience of mandatory criminal action. However, the research sought to analyze empirical data and not just arguments of rhetoric, and established comparisons between the routine and results obtained by Public Prosecutors who adopt the finalist theory (more traditional) and the functionalist (more innovative), verifying that the functionalism has better Results with fewer processes, because it focuses on the system as a whole. It also addressed foreign laws and practices, verifying that functionalism currently prevails in practically all countries, except in Brazil. In addition, even in countries that do not expressly guarantee functional independence to members of the Public Prosecutor's Office, they have the authority to establish criminal public policy priorities and results. Thus, the Code of Criminal Procedure must conform to the Federal Constitution and not the contrary, which implies a revision of articles 24 and 28 of the CPP, and for this the work elaborated a whole research on the ends of criminal law, On criminology, on criminal policy, on criminal action, including historical aspects of criminal law and criminal procedure in Brazil, as well as pointed out that several writers defend the opportunity of criminal action, which is little discussed in the most used works in undergraduate courses Of Law, and finally, stressed the need that the works of Criminal Procedure also address and confront Constitutional Law with the Criminal Procedure of 1941